Tourniquet-induced ischaemia-reperfusion injury: the comparison of antioxidative effects of small-dose propofol and ketamine - Omer,Karaca (2017)
Abstract Objectives: The aim of the present study was to investigate the preventive effects of propofol and ketamine as small dose sedation during spinal anaesthesia on tourniquet-induced ischaemia-reperfusion injury. Methods: 30 patients were randomly assigned into two groups of 15 patients. In the propofol group, sedation was performed with propofol 0.2 mg·kg-1 followed by infusion at a rate of 2 mg·kg-1·h-1. In the ketamine group, a continuous infusion of ketamine 0.5 mg·kg-1·h-1 was used until the end of surgery. Intravenous administration of midazolam was not used in any patients. Ramsay sedation scale was used for assessing the sedation level. Venous blood samples were obtained before propofol and ketamine infusion (T1), at 30 minutes (min) of tourniquet ischaemia (T2), and 5 min after tourniquet deflation (T3) for malondialdehyde (MDA) measurements. Results: No differences were noted between the groups in haemodynamic (p > 0.05) and demographic data (p > 0.05). There was no statistically significant difference between the two groups in terms of T1, T2 and T3 periods (p > 0.05). There was a statistically increase observed in MDA values respectively both in Group P and Group K between the reperfusion period (1.95 ± 0.59, 2.31 ± 0.48) and pre-ischaemia (1.41 ± 0.38, 1.54 ± 0.45), and ischaemia (1.76 ± 0.70, 1.71 ± 0.38) (µmoL-1) periods (p < 0.05). Conclusions: Small-dose propofol and ketamine has similar potential to reduce the oxidative stress caused by tourniquet-induced ischaemia-reperfusion injury in patients undergoing arthroscopic knee surgery under spinal anaesthesia.